2011
DOI: 10.2341/10-173-c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Prolonged Application Time of an In-office Bleaching Gel

Abstract: By refreshing the in-office bleaching gel at each clinical appointment, clinicians can improve the bleaching speed and reduce tooth sensitivity rates. SUMMARYObjective: The aim of this study was to evaluate whether the use of a gel applied for 1 3 45 minutes would have the same bleaching rate and tooth sensitivity levels when compared with 3 3 15-minute applications.Methods: In-office bleaching was performed in 30 participants with 35% hydrogen peroxide gel. In one group (n=15; 3315 minutes), the bleaching age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 20 publications
(27 reference statements)
6
91
2
3
Order By: Relevance
“…An equivalent and significant tooth color enhancement was observed in both study groups. The degree of whitening obtained in this study is similar to that reported in other clinical trials 9,17,19 and also in the literature review. 1 Finally, it should be mentioned that only a value-oriented shade g uide was used for identification of color changes throughout the study period.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…An equivalent and significant tooth color enhancement was observed in both study groups. The degree of whitening obtained in this study is similar to that reported in other clinical trials 9,17,19 and also in the literature review. 1 Finally, it should be mentioned that only a value-oriented shade g uide was used for identification of color changes throughout the study period.…”
Section: Discussionsupporting
confidence: 80%
“…9,12,17,20 Tooth sensitivity was not reduced by previous application of a nano-calcium phosphate paste; thus, preventing us from rejecting the first null hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Reis and others 12 reported contradictory results in their recent clinical trial. In-office bleaching was performed in 30 participants with 35% hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 95%